The Influence of Androgens on Paralysis in Mice Following Intravenous Inoculation of Herpes Simplex Virus - Yirrell, D. L.; Blyth, W. A.; Hill, T. J. (Journal of General Virology, 1987)
Summary In mice, intravenous inoculation of relatively avirulent strains of herpes simplex virus [e.g. P2C6, a mutant of strain CL(101), deficient in thymidine kinase] produced infection in the adrenal gland and mid-spinal cord followed by hind limb paralysis without death. Male mice were less susceptible to paralysis than female mice. Castration of male mice before inoculation increased their susceptibility to that of female animals; treatment with testosterone reversed this change. The differences in susceptibility to paralysis in the various categories of animal were not reflected in differences in growth of virus in the adrenal gland or spinal cord.
Keywords: paralysis